Designing Mobile Interface for Elderly - Nur Rahmah, Zulkifli (2010)
At the moment, mobile phones have becoming necessity used by people all over the world. This scenario has been proven by several studies that shown the increment of mobile phones usage. In keeping and increasing the number of mobile phone users, the mobile phone application interface usability is crucial, especially for elderly. Elderly have a difficulty in using a mobile phone application with a design that is difficult to understand. This is due to problems in their vision, motivation, physical and cognitive aspects. Apart from that, other problems that been faced is the sensory impairment. The problems faced by them can be coped through the study in the mobile phone interface design in order to define the suitable interface for the use of elderly. Objective of this study is to define the characteristic in interface for mobile application interface design especially to the elderly. Prototype has been designed according to characteristic that been classified. User Centered Design is been used as the methodology, while usability test have been used as the testing for this study. In order to define the user satisfaction, questionnaires have been given during the testing. The data that been obtained shows the characteristics are important in designing the mobile application interface for elderly.